The level of acquisition of historical concepts for tenth and eleventh grade literary branch students from the perspective of history teachers (Raparin Journal of Humanities (RJH), 2024)
The purpose of this research is to prepare an appraisal criterion about the pitch of acquisition of historical concepts in the first and second parts of the history book of tenth and eleventh grades of literary branch students. At the same time, displaying the problem of foreshowing the concepts to students by some of teachers in Chamchamal Education Directorate. In order to hit the aim of the research, the researcher used the attributive analysis content method of. First of all, the researcher differentiated all of the historical concepts of the three vessel (pure, interim and spatial) of the first and second parts of the history book of the tenth and eleventh literary branch. Then preparing (60) multiple questions, which (30) questions were prepared for tenth grade students and (30) questions for eleventh grade students for both genders of males and females of the academic year (2022 - 2023). The tenth grade students of literary branch in Chamchamal education consisted of (621) boys and (399) girls, generally, the students of both genders in the tenth grade of literature consisted of (1020) students who were divided into (17) schools. However, the students of the eleventh grade of literature in Chamchamal consisted of (288) boys and (271) girls. In total, the students of both genders in the tenth grade of literary consisted of (559) students who were divided into (20) schools in the abuttals. Thus, the total number of students in the tenth and eleventh grades of literary brunch in governmental schools of the Chamchamal Education Directorate, The number of students in the region reaches (1579) students. It includes (909) male students and (670) female students. Then the researcher assigned the validity and stability of the devices according to Person's equations, arithmetic mean, test (T. test), after verifying the validity of the tool, The researcher used the statistical program (SPSS). As a result, The researcher discovered that all the historical concepts of the first and second parts of the history of the tenth and eleventh grades with all of the three vessel (pure, interim and spatial)  and can be used as a criterion and get benefit from them for the other researches.